VARIATIONS IN METADISCOURSE USE IN ENGLISH LANGUAGE INTRODUCTION AND LITERATURE REVIEW THESIS CHAPTERS - Osei Yaw Akoto; Joseph Benjamin A. Afful (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
Studies have established that thesis chapters are both similar and dissimilar with respect to their rhetorical choices. This paper examined metadiscourse use in the Introduction and Literature Review (LR) chapters of English Language theses from a nonnative context. The Introduction and LR chapters of ten theses, resulting in 50, 000 and 100, 500 words respectively, constituted the data sets for this study. Drawing on Hyland’s metadiscourse model, we manually coded all the metadiscursive elements. The study reveals statistically significant differences across all the interactive and interactional subcategories, affirming the stance that the rhetorical function of a thesis chapter influences its metadiscoursal choices. The study also found a new subcategory of meta-discoursal category labeled continuants. The paper has implications for the teaching and supervision of postgraduate theses, and the theory of metadiscourse.